2013
DOI: 10.2172/1110479
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Technetium Speciation in Cast Stone

Abstract: Executive SummaryThis report describes the results from laboratory tests performed at Pacific Northwest National Laboratory (PNNL) for the U.S. Department of Energy (DOE) EM-31 Support Program (EMSP) subtask, "Production and Long-Term Performance of Low Temperature Waste Forms" to provide additional information on technetium (Tc) speciation characterization in the Cast Stone waste form. To support the use of Cast Stone as an alternative to vitrification for solidifying low-activity waste (LAW) and as the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…By comparison, only 0.015 and 0.167 meq are needed to reduce the Tc(VII) present in 100 mL for the C1 and C3 tests, respectively. The reduction capacity for BFS1 and BFS2, which was measured using the Ce(IV) methodology of Angus and Glasser (1985), was 0.793 and 0.800 meq/g [Um et al (2012[Um et al ( , 2013], and 0.884 and 0.725 meq/g [Langton et al (2013)], 2 respectively. Because only 1 g of getter material was used in the experiments conducted at a 1:100 getter-to-LAW simulant ratio, there was insufficient reduction capacity to reduce all of the Cr and Tc present in the LAW simulant.…”
Section: Behavior Of Other Elements Present In the Simulantmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparison, only 0.015 and 0.167 meq are needed to reduce the Tc(VII) present in 100 mL for the C1 and C3 tests, respectively. The reduction capacity for BFS1 and BFS2, which was measured using the Ce(IV) methodology of Angus and Glasser (1985), was 0.793 and 0.800 meq/g [Um et al (2012[Um et al ( , 2013], and 0.884 and 0.725 meq/g [Langton et al (2013)], 2 respectively. Because only 1 g of getter material was used in the experiments conducted at a 1:100 getter-to-LAW simulant ratio, there was insufficient reduction capacity to reduce all of the Cr and Tc present in the LAW simulant.…”
Section: Behavior Of Other Elements Present In the Simulantmentioning
confidence: 99%
“…The obvious implication of Oblath's (1984) and Langton's (1988) studies, and many more recent ones, is that the BFS has reduced the Cr(VI) and Tc(VI) species to their much more insoluble Cr(III) and Tc(IV) species. To quantify the reducing capacity of BFS, as well as the other two ingredients cement and fly ash, Roberts and Kaplan (2009), Kaplan et al (2008), Um et al (2012Um et al ( , 2013, and Langton and Almond (2013) measured the reductive capacity of the dry blend ingredients used in Cast Stone and Saltstone. They found that the BFS has a large reductive capacity (~790 to 820 μeq g -1 ) compared to Portland cement (198 μeq g -1 ) and fly ash (299 μeq g -1 ).…”
Section: A41 Blast Furnace Slag -Tc Reductant (Or Getter)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these data were updated in the FY 2014 Special Analysis for the Saltstone Disposal Facility at the SRS (SRR CWDA 2014). Reductive capacity data from Um et al (2013) are included as well. In general, this data review is focused on the most recent LSW grout formulation work and Cast Stone data with secondary wastes and LAW simulants.…”
Section: Data Sources Included In the Reviewmentioning
confidence: 99%
“…Reduction capacity measurements have been made on the same 26 Cast Stone waste forms made with LAW simulants that were studied by Westsik et al (2013). These results were reported in Um et al (2013), and are shown in Table 3.8.…”
Section: Reductive Capacity Of Cast Stonementioning
confidence: 99%